2012
DOI: 10.1055/s-0032-1329211
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action in primary hyperaldosteronism before and after surgical or pharmacological treatment

Abstract: The relationship between arterial hypertension and insu lin resistance has long been established. We used primary hyperal dosteronism as a model of the relationship between secondary hy pertension and insulin sensitivity. Our group consisted of 9 patients with arterial hypertension caused by primary hyperaldosteronism. Five of these patients with aldosterone producing adenoma were operated on and four patients with idiopathic hyperaldosteronism were treated with spironolactone. Hyperinsulinaemie euglycaemic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 15 publications
(18 reference statements)
1
37
0
4
Order By: Relevance
“…The largest study in the field (21), including 460 patients with PA and 1363 controls with essential hypertension reported no differences regarding proportions of hyperglycemia or fasting glucose levels. On the other hand, there is evidence that patients with PA have a disturbed glucose metabolism (13,16,18,19). Thirty PA patients had higher glucose, lower C-peptide levels and lower HOMA-bF index than 60 patients with essential hypertension (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest study in the field (21), including 460 patients with PA and 1363 controls with essential hypertension reported no differences regarding proportions of hyperglycemia or fasting glucose levels. On the other hand, there is evidence that patients with PA have a disturbed glucose metabolism (13,16,18,19). Thirty PA patients had higher glucose, lower C-peptide levels and lower HOMA-bF index than 60 patients with essential hypertension (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings are inconsistent (12,13,14,15,16,18,19,21). Two smaller studies (nZ24 (14) and 63 subjects (15)) and one large study (nZ1823 subjects (21)) reported no association between PA and glucose metabolism (including insulin sensitivity index, HOMA, or quantitative insulin sensitivity check index (QUICKI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fischer et al showed that adrenalectomy for APA (n = 9) did not affect the index of insulin resistance, assessed using the insulin clamp method [7]. Two other studies reported that improvements in insulin sensitivity were observed in patients with APA after adrenalectomy, but not in patients with idiopathic adrenal hyperplasia treated with MR-antagonists [23,24]. The limited number of patients and the different study protocols used may explain the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Определенную роль в реализации данного со-стояния играет гипокалиемия, часто сопровождаю-щая гиперальдостеронизм. Подробный механизм этого влияния до конца не изучен, более того, он опровергается рядом авторов [45], которые наблю-дали прогрессирование инсулинорезистентности у пациентов с ПГА, несмотря на инфузию калия.…”
Section: альдостерон и инсулинорезистентностьunclassified